The ER membrane-anchored ubiquitin ligase Hrd1 is a positive regulator of T-cell immunity - Yuanming Xu; Fang Zhao; Quan Qiu; Kun Chen; Juncheng Wei; Qingfei Kong; Beixue Gao; Johanna Melo-Cardenas; Bin Zhang; Jinping Zhang; Jianxun Song; Donna D. Zhang; et al. (Nature Communications, 2016)
Hrd1 is an E3 ubiquitin ligase involved in ER-associated degradation and MHC I turnover. Here the authors use T-cell-specific ko mice and a mouse model of multiple sclerosis to show that Hrd1 also drives pro-inflammatory T helper cell responses and contributes to pathogenesis of autoimmune disease.